Kritik Out Put Pesantren Terhadap Santri Pada Era Digitalisasi - Aris Nurlailiyah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2020)
The history of Islamic development in Indonesia is not separated from the history of pesantren, because pesantren is one of the oldest educational institutions in the archipelago that has existential power in javanese pattern and understanding of islam and integration in existing social structures. In the beginning, pesantren had the purpose that students receive religious ethics above other ethics, then had a fundamental interest to instill islamic scientific tradition and give them an understanding that learning is solely an obligation and devotion to God, not to pursue the interests of power, money and earthly majesty. But in this modern era those goals need to be re-constructed, such as clearly defining what a good and ethical sense of morality is. Graduates who are purely from pesantren are challenged by various things, such as in job prospects and authority in the community. This paper will explain about pesantren output in the midst of the flow of digitization. Keywords: pesantren, santri, out put pesantren, digital age